2008
DOI: 10.1007/s10593-008-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Methyl nitroacetate and 3-nitropropionate in the synthesis of hexahydropyrimidines and piperidines

Abstract: Treatment of methyl nitroacetate and 3-nitropropionate with formaldehyde and primary amines underMannich reaction conditions gives 5-nitrohexahydropyrimidines. In the case of methyl nitroacetate both the 5-nitrohexahydropyrimidine and isomeric 3,5-di(methoxycarbonyl)-1-methyl-3,5-dinitropiperidines are formed.The reaction of primary amines and formaldehyde with compounds containing a mobile hydrogen atom on a carbon atom is widely used in organic synthesis as a convenient method for preparing tetrahydro-1,3-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This methodology was later expanded by Shakirov et al to include reaction of methyl nitroacetate. 42 Similar reactions have also been reported by Cichra and Adolph. 43 Hirst et al showed that similar chemistry could be used for synthesis of 5-nitro-tetrahydro-1,3-oxazines 25 (Scheme 14).…”
Section: Heterocycle Synthesissupporting
confidence: 77%
See 1 more Smart Citation
“…This methodology was later expanded by Shakirov et al to include reaction of methyl nitroacetate. 42 Similar reactions have also been reported by Cichra and Adolph. 43 Hirst et al showed that similar chemistry could be used for synthesis of 5-nitro-tetrahydro-1,3-oxazines 25 (Scheme 14).…”
Section: Heterocycle Synthesissupporting
confidence: 77%
“…Using an additional equivalent of formaldehyde the nitrodiamine intermediates 24 underwent cyclization via condensation with formaldehyde to form the 5-nitro-hexahydro-1,3-pyrimidines 23 . This methodology was later expanded by Shakirov et al to include reaction of methyl nitroacetate . Similar reactions have also been reported by Cichra and Adolph …”
Section: Early Developmentsmentioning
confidence: 65%